Culture, religion, and conspicuous consumption-nexus triad fueling food waste - Akor, Sunday Joseph; Adegbola, Adetayo Jacob; Adegbola, Rukayat Queen; Sulyman, Abdulazeez; Sanni, Lateef Oladimeji (Social Agriculture, Food System, and Environmental Sustainability, 2025)
Background: This narrative review offers vital contribution to the discourse on sustainability, food security, and sociocultural transformation; it furnishes a compelling interdisciplinary exploration of the complex drivers of food waste in Nigeria. It highlighted how in Nigeria, the phenomenon is a multifarious issue profoundly rooted in the country’s cultural norms, religious practices, celebrations, exacerbated by excessive consumerism, conspicuous consumption and lavish spending particularly during festivals and religious ceremonies. Furthermore, the article alluded that the background of the problem transcends logistical inefficiencies or lack of infrastructure; they are complexly tied to societal values and perceptions of status and hospitality. Methods: This article uses comparative analytical lenses to synthesize existing literature to provide an intricate and balanced consideration of diverse issues that have relevance to the phenomenon under consideration. Multiple data sources, especially academic databases such as ResearchGate, DOAJ, Scopus, and JSTOR were searched for relevant studies and articles that have bearing on food wastage. The review is hinged on the theory of Planned Behavior and Social Practice Theory. Findings: In line with the tenents of theory of Planned Behavior this review especially revealed that food wastage occur among individuals and households in Nigeria because people believe food wastage is innocuous, a sign of abundance and hospitality. Also, corroborating the Social Practice Theory, this review uncovered that food wastage in Nigeria is largely related to everyday routines and skills that shape how people buy, store, cook, and consume food. Conclusion: This article concluded that food wastage issue in the country is driven not by the surplus or low cost of food but mostly by the caprices of individuals. As a departure from other articles and research on the phenomenon, this article has put plate food waste and misjudging food quality on a pedestal as also weighty factors that contribute subtly but significantly to the food waste phenomenon in the country. The article recommended amongst others that food waste reduction should tackle issues across the entire supply chain, from preparation to consumer behavior while emphasizing the need to discard outdated and inefficient practices and reevaluate cultural norms around celebrations and religious festivals. Novelty/Originality of this article: Majority of contemporary articles on food wastage focused chiefly on factors such as poor storage facilities and supply chain inefficiencies, with little to no attention given to the social causation of the phenomenon which is a primary focus of this review.